Community Economic Empowerment Through the Syirkah Principle: A Case Study of Farmers in Padang Pariaman Regency - Efendi, Erizal Candra; Mustika, Ruri; Hadi, Wildan (Denisya Smart Consulting, 2025)
This study explores the application of the syirkah (partnership) principle as a model for community economic empowerment among farmers in Padang Pariaman Regency, West Sumatra. Rooted in Islamic economic ethics, syirkah emphasizes fairness, transparency, and shared risk between capital providers, farmers, and community leaders. Using a qualitative case study design, data were collected through in-depth interviews, focus group discussions, and participatory observations involving farmer groups, Islamic cooperatives (Baitul Maal wat Tamwil), and local religious figures. The findings reveal that syirkah enhances access to productive capital, increases agricultural yields by 25–30%, and improves household income stability while strengthening social cohesion and mutual trust among participants. The partnership structure fosters ukhuwah iqtishadiyah (economic brotherhood) and fulfills the objectives of maqasid al-shariah by integrating economic welfare with moral responsibility. However, sustainability challenges remain, particularly in financial management skills, market access, and generational continuity. Strengthening institutional literacy, digital integration, and youth participation are therefore crucial for scaling up syirkah-based empowerment. Overall, the study concludes that syirkah serves not only as an Islamic financial instrument but also as a transformative framework that bridges spirituality, cooperation, and sustainable rural development.